Global food prices, regime type, and urban unrest in the developing world. (March 2015) - Hendrix, Cullen S; Haggard, Stephan
The 2014 IPCC report concludes that changes in precipitation and temperature could cause global food prices to nearly double by 2050. Anecdotal evidence of riots during the global food price spikes of 2007–08 and 2010–11 raises the more general question of whether global food prices affect patterns of contentious politics in developing countries. Drawing on a dataset of urban unrest in 55 major cities in 49 Asian and African countries for the period 1961–2010, we find the effect of global food prices on protests and rioting is contingent on regime type: democracies are more prone to urban unrest during periods of high food prices than autocracies. We show that this is due both to the more permissive political opportunity structure in democratic systems and to systematic differences in food policy across regimes of different types. Relative to autocracies, democracies pursue policies that are more favorable to the rural sector and less favorable to the cities. The findings have longer-run implications. To the extent that climate change will make many developing countries more dependent on food imports, and that prices could rise and be more volatile, we suggest another vector by which climate change may affect political unrest. Our findings highlight the importance of both political institutions and policy choices in mediating global shocks.